Persepsi Masyarakat di Sekitar Maha Vihara Majapahit Terhadap Toleransi Sebagai Faktor Penerimaan Keberagaman Budaya dan Agama - Ramadhan, Ike; Eliza, Nidya; Sadrai, Maharani Putri; Kamila, Shaffa Cahya; Taufikurrahman, Taufikurrahman; Wibawani, Sri; Mandyartha, Eka Prakarsa (PT. Riset Press International, 2024)
Indonesia is a country that has cultural and religious diversity. This research aims to analyze the perceptions of the people around Maha Vihara Majapahit regarding tolerance as a factor in accepting cultural and religious diversity. Through qualitative interview methods, data was obtained from a number of sources to provide the views of visitors who visited this site. The research results show that the surrounding community's perception of tolerance plays an important role in encouraging acceptance of cultural and religious diversity. Factors such as education, experience of intercultural interactions, and religious values influence an individual's perception of tolerance. These findings have important implications in efforts to promote intercultural harmony and religious diversity in society. Further research could explore effective strategies to increase positive perceptions of tolerance in various cultural and religious contexts.